Thymoquinone attenuates doxorubicin-induced lung damage via heat shock proteins, inflammation and endoplasmic reticulum stress - Öztürk, E; Kaymak, E; Akin, AT; Karabulut, D; Yakan, B (Journal of the Hellenic Veterinary Medical Society, 2023)
The aim of this study is to determine possible therapeutic effects of THQ on doxorubicin induced lung damage in rats. Rats were divided into five groups (n = 8): control, THQ, olive oil, DOX (a single dose of 15 mg/kg intraperitoneally (i.p.) on seventh day of the experiment), and DOX+THQ (10 mg/kg THQ per day and 15 mg/kg DOX i.p. on seventh day). Animals were euthanized, and lung tissues were evaluated histopathologically. Caspase3, GRP78, GADD153, HSP90, HSP70, PCNA, COX2 and TNFα immunostaining were performed to determine the expression levels of these proteins among groups. TUNEL method was used for evaluation of apoptotic index. Moreover, total antioxidant status (TAS), total oxidant status (TOS) and IL6 in lung tissue were measured by ELISA assay. The DOX group had histopathological deterioration compared to the control group. There was an increase in apoptotic index, caspase 3, GRP78, GADD153, HSP90, HSP70, PCNA, COX2 and TNFα expressions in the DOX group. While TAS level of the DOX group decreased, IL6 and TOS level increased when compared with the other groups. However, there was improvement in lung tissue in DOX + THQ group compared to the DOX group. There was a decrease in apoptotic index, caspase 3, GRP78, GADD153, HSP90, HSP70, PCNA, COX2, TNFα expressions and TOS, IL6 in DOX+THQ group compared to the DOX group. We suggest that THQ can be used as a protective agent to reduce the toxic effects of DOX.